(untitled) (Journal of University of Babylon for Engineering Sciences, 2023)
Welding joints of materials that are difficult to weld with traditional methods, particularly polymeric materials, require friction stir welding (FSW). In this research, two types of polymers have been used to study the effect of friction stir welding (FSW) parameters on the properties of dissimilar polymer joints. High density polyethylene (HDPE) and polyvinyl chloride (PVC) plates with dimension of (5x100x200 mm) were welded by using milling machine as friction stir welding machine. The welding tool was used with shoulder diameter of (18 mm) and pin diameter of (6 mm) with height of (4.8 mm). The rotation speed was applied in the range of (340 to 1660 rpm) with welding linear speed of (24 and 40 mm/sec). The result shows that the hardness was increased with increasing rotational speed until (850 rpm) then decreased when the welding speed equal to (24 mm/sec). However, its decreased with increasing welding linear speed when it became (40 mm/sec). In addition, the maximum hardness and tensile strength was found at rotational speed equal to (495 rpm) and welding linear speed equal to (24 mm/sec) which equal to hardness of (72 Shore D) and tensile strength of (39 MPa). Finally, the result displays that there is an opportunity to weld dissimilar polymers.